2004
DOI: 10.1038/sj.jea.7500362
|View full text |Cite
|
Sign up to set email alerts
|

Exposure–response relationships between lifetime exposure to residential coal smoke and respiratory symptoms and illnesses in Chinese children

Abstract: Data collected in a large epidemiologic study were analyzed to examine respiratory health effects of residential coal use in 7058 school children living in the four Chinese cities of Chongqing, Guangzhou, Lanzhou, and Wuhan. A Scenario Evaluation Approach was used to develop two exposure variables, heating coal smoke and cooking coal smoke. Estimated lifetime exposures to heating coal smoke and cooking coal smoke were both classified into fourlevel ordinal scales, as follows: no reported exposure (control); li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…When lifetime exposures to coal smoke from heating were classified according to four ordinal levels (no, light, moderate, and heavy exposure), monotonic and positive exposure–response relationships were observed for OR estimates of phlegm, cough with phlegm, and bronchitis. In addition, OR estimates for cough, wheeze, and asthma were all > 1 in the exposed groups relative to the no-exposure group (Qian et al 2004). …”
Section: Health Effectsmentioning
confidence: 99%
“…When lifetime exposures to coal smoke from heating were classified according to four ordinal levels (no, light, moderate, and heavy exposure), monotonic and positive exposure–response relationships were observed for OR estimates of phlegm, cough with phlegm, and bronchitis. In addition, OR estimates for cough, wheeze, and asthma were all > 1 in the exposed groups relative to the no-exposure group (Qian et al 2004). …”
Section: Health Effectsmentioning
confidence: 99%
“…Of the seven respiratory conditions/diseases analyzed in the hospital records in the present study, cough, wheeze, and asthma were all significantly associated with indoor coal combustion in a previous epidemiological investigation of children in China [18]. Another report found that susceptibility to bronchitis was significantly associated with ambient PM 2.5 and polycyclic aromatic hydrocarbons (PAHs) among children in a former coal mining area in the Czech Republic with numerous large coal-fired power plants [18].…”
Section: Introductionmentioning
confidence: 88%
“…Another report found that susceptibility to bronchitis was significantly associated with ambient PM 2.5 and polycyclic aromatic hydrocarbons (PAHs) among children in a former coal mining area in the Czech Republic with numerous large coal-fired power plants [18]. Interestingly, von Mutius et al [19] noted a protective effect of in-home coal burning for children at risk of developing hay fever or other immunoglobulin E antibody-mediated allergies in southern Germany.…”
Section: Introductionmentioning
confidence: 99%
“…This means that children will inhale more pollutants indoors, which seriously affects their health and overall performance [ 9 , 10 ]. In recent years, much work has focused on the risk of cancer in children exposed to PAHs as well as the time–spatial distribution of pollutants [ 11 , 12 ] and exposure–response relationship between air pollution levels and mortality/morbidity [ 13 , 14 , 15 ]. The exposure pathway of PM may have a potential impact on children [ 16 ].…”
Section: Introductionmentioning
confidence: 99%